The more economic approach to the application of EU merger control - Zalewska-Głogowska, Marta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
In general terms, the more economic approach to the application of EU merger law implies increased reliance on theoretical concepts from industrial economics and quantitative methods of analysis, firstly in the case of investigations and, secondly, when formulating legislation and defining the criteria that are to be set. In other words, a tendencyof the more economic approach to EU merger control is to base the evaluation of each specific case on an assessment of its anti- and pro-competitive effects (effects-based approach), rather than on the form of the intrinsic nature of a particular practice (formbased approach). In this article, the author presents the development of the more economic approach to the application of EU merger control and analyses the implications of this new trend which is present in the European Commission’s practice.